“Duct-Road Sign”: Differentiating Pancreatic Neuroendocrine Tumors from Pancreatic Ductal Adenocarcinomas - Bo Xiao; Zhi-Qiong Jiang; Jin-Xiang Hu; Xiao-Ming Zhang; Hai-Bo Xu (New Horizons in Medicine and Medical Research Vol. 10, 2022)
The present study hypothesis highlights the presence of potential signs of the main pancreatic duct (MPD) in this setting, particularly in atypical (nonhypervascular) PNETs, which would aid in their differential diagnosis along with preventing misdiagnosis. Thus, the current study was conducted to find potential imaging signs of the MPD in MRI for PNETs. This retrospective study was approved by institutional review boards of our 2 tertiary hospitals. The study was performed in accordance with the Helsinki Declaration of 1983; however, the requirement for informed consent was waived due to the retrospective nature of the study. A Spearman correlation coefficient (r) was calculated to test the relationship between MRI diagnosis for PNETs and the frequency of appearance of duct-road sign at MRI. The duct-road sign, as a criterion for PNET, had a sensitivity of 84% and specificity of 100% for the purpose of differentiating PNETs from PDACs in a broad sense. If the duct-road sign was defined as “typical curved road sign” of type II in the narrow sense, the specificity was also 100%. Furthermore, when the enhancement of PNET is atypical (heterogeneous and nonhypervascular on MRI), the duct-road sign could also be considered a valuable indirect feature in this setting. Consequently, we recommend this new imaging sign—duct-road sign—like “different pathways of the MPD” which may be a helpful sign correlating PNETs instead of PDACs. Apart from standard imaging findings, the duct-road sign closely correlates with the differential diagnosis of PNET and may be useful in separating PNETs from PDACs. In addition, TDR analysis with a point > 7.7 in MRI could be used to diagnose PNET rather than PDAC.